ANALISIS PEMASARAN SAPI POTONG - Nur Afni Lasaharu; Yuriko Boekoesoe (Jambura Journal of Animal Science, 2020)
The purpose of this study was to determine the marketing analysis of beef cattle in Taluditi Regency, Pohuwato Regency. Gorontalo. The research method uses the survey method. The data used in this study are primary data with data collection techniques conducted through observation, interviews, and documentation. Sampling is determined through stratification of Random Sampling, where the sample is based on the largest population. The number of samples produced was 72 respondents. Data were analyzed descriptively. The observed variables are marketing channels, marketing margins and marketing efficiency. The findings of this study are two beef cattle marketing channels in Taluditi District, Pohuwato Regency, namely: Channel I (Farmers - Collector Traders - Consumers), and Channel II are (Breeders - Collector Traders - Retailers Traders - Consumers). The average marketing margin in each marketing institution is Rp. 100,000 - Rp. 500,000. The level of marketing efficiency in each marketing institution is 0.26-3.1